Resilience, emotions, and suicidal ideation in Mexican adolescents during COVID-19 pandemic: risk factors and protective mechanisms - Puig-Lagunes, Ángel Alberto; Varela-Castillo, Guerson Yael; Rodríguez-Landa, Juan Francisco; Ortiz-Cruz, Fabiola; German-Ponciano, León Jesús (Frontiers in Psychiatry, 2024)
Introduction. Suicide is the second leading cause of death among adolescents worldwide. Suicidal ideation (SI) in adolescents may be influenced by factors such as resilience, anxiety, and depressive symptoms. The COVID-19 pandemic served as a significant stressor with documented impacts, yet further research is needed to clarify its effects. While stressful events are known to be associated with increased SI, direct evidence linking COVID-19 specifically to elevated SI remains limited.Objective. The aim of this study was to identify the risk and protective factors associated with SI in Mexican adolescents during the COVID-19 pandemic. Method. A cross-sectional, correlational descriptive study was conducted between May and June 2022 with a sample of 2,194 high school students, with a mean age of 16.6 years (SD = 1.2). Among the participants, 58.9% were female and 41.1% were male. They completed inventories to assess stress, anxiety, depressive symptoms, and resilience. Results. Of 2194 adolescents, 15.5% presented SI, with females showing a higher prevalence of SI, anxiety, and depressive symptoms compared to males. In contrast, resilience was lower in females. Furthermore, depressive symptoms were identified as a risk factor for SI (OR 1.212; 95% CI 1.186, 1.240), whereas social competence was highlighted as a protective factor (OR 1.046 95% CI 1.044, 1.078). Conclusions. The findings underscore the importance of preventing SI in adolescents by addressing anxiety and depressive symptoms, which were identified as risk factors, and by promoting social competence as a protective factor. Therefore, an integrated approach that addresses both individual mental health and the social context must be considered for preventing SI in adolescents.